ANALISIS PENGARUH PROFITABILITAS (ROA), LIKUIDITAS (CR), SALES GROWTH DAN FIRM SIZE TERHADAP STRUKTUR MODAL DENGAN TANGIBILITY ASSET DAN FIRM AGE SEBAGAI VARIABEL KONTROL (Studi Kasus pada Perusahaan Subsektor Dagang Eceran Yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2017) - Pramesti, Prisca Regita; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to examine the effect of variable of profitability (ROA), liquidity (CR),sales growth and firm size on capital structure with tangibility asset and firm age as controlvariable.The population in this study were retail trade sub-sector companies that were listed on theIndonesian Stock Exchange in 2013 – 2017. The sample technique used was purposive sampling.So that a sample of 12 companies was obtained, thus obtained 60 research data. The analysistechnique used is multiple linear regression using the classical assumption test and regressionanalysis with a significance level of 5%.Based on the results of research that simultaneously uses the F test variable profitability,liquidity, sales growth, firm size, tangibility asset and firm age as control variable significantlyinfluence the capital structure. The result of partial testing using the T test show that profitability,liquidity, firm size, tangibility asset and firm age have a negative and significant effect on capitalstructure. While sales growth has a positive and insignificant effect on capital structure and theresult of control variables there are tangibility asset and firm age are -3,223 with the significantcy0,001 and -3,915 with the significantcy 0,003 so tangibility asset and firm age has a negative andsignificant effect on DER. Determination of coefficient R2 of 0,471 shows that 47,1% of thevariation of the DER is explained by the independent variables in the study while the remaining52,9% is explained by other variables outside the research.